(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the impact of the service industry on the quality of life of the population. The study examines the relationship between service sector development and various socio-economic indicators, such as income levels, employment rates, and access to essential services. The research utilizes statistical data, comparative analysis, and graphical representations to illustrate the findings. The study concludes that a well-developed service sector contributes positively to economic growth and social well-being.